Fe2o3/Nio Nanocomposites: Synthesis, Characterization and Roxarsone Sensing by Fourier Transform Infrared Photoacoustic Spectroscopy - Santander-Meyer, R (Royal Society of Chemistry, 2023)
The Fe2O3/NiO nanocomposite was prepared through facile mixing of pure Fe2O3 and NiO nanoparticles. Pure metal oxides were synthesized by the glycine aided hydrothermal method. The crystal structure was determined by X-ray diffraction (XRD) analysis. Both scanning electron microscopy (SEM) and transmission electron microscopy (TEM) clearly show that the NiO nanospheres were homogeneously distributed on Fe2O3 nanoplates. Fourier transform infrared (FTIR) spectra reveal that functionalization by glycine induces carboxylic and amino groups on the surface of nanoparticles. The optical properties such as light absorption behavior and band gap of the Fe2O3/NiO nanocomposite were determined by UV-Visible diffuse reflectance spectroscopy (DRS UV-Vis). The roxarsone (ROX) sensing behavior of the Fe2O3/NiO nanocomposite was evaluated by using Fourier transform infrared (FTIR) - photoacoustic spectroscopy (PAS) that allowed quantitative sensing of the ROX@Fe2O3/NiO complex. The photoacoustic signals of ROX were clearly observed in the FTIR-PAS spectra, particularly in the range of 1700 to 1000 cm−1 without spectral interference from the composite. Furthermore, principal component analysis (PCA) and partial least square (PLS) regression models were applied to calibrate and validate ROX quantification. The PLS model exhibited the best performance in predicting the ROX concentration through ROX@Fe2O3/NiO samples. This proof of concept suggests that the Fe2O3/NiO nanocomposite has improved adsorption and spectral features by FTIR-PAS for sensing of organometallic compounds such as ROX. © 2023 The Royal Society of Chemistry.